THE LEGAL BASIS FOR LEASING AIRCRAFT EUIPMENT - Веприняк, Д. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In this article the author focuses on the legal basis of aircraft leasing in Ukraine, in the conditions of leasing operations and the algorithm of using the opportunities offered in connection with the application of the provisions and norms of these legal documents.